Mikropropagasi Ramin (Gonytilus bancanus(Miq) Kurz) dari Eksplan Batang satu buku secara in Vitro - Yelnititis Yelnititis; Tadjudin Edy Komar (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2011)
Ramin (Gonystylus spp.) is one of the genus wood producing that interested to trade. This plant growth in peat swamp forest areas. This genus consist more than 20 species and only Gonystylus bacanus (Miq.) Kurz) has been explored. From 2004 this species has been listed in CITES APPENDIX II. Propagation of this plant can conducted trhrough generative but difficult to get of materials as explants. Murashige and Skoog (MS) medium used as growth medium. The observation was made on Shoot induction period, shoot number, heigh of shoot and visual performance of culture produced. The results showed that shoot can induced from stem with single node. The treatment of 2.0 mg/l thidiazuron is the best treatment to shoot induction. The average of shoot find was 5.1 days after cultured and faster than other treatment. The treatment of 0.5 mg/l BA is the best to shoot growth and visual performance. Average of shoot height from this treatment is 0.7 cm. The treatment of 0.5 mg/l BA on modifild MS medium is the best to shoot elongation than MS medium.